Down Syndrome associated to Moyamoya Syndrome: Case report (Research, Society and Development, 2022)
Moyamoya syndrome (MMS) is a rare cerebrovascular condition that primarily affects female people of Japanese origin. Moyamoya is a term of Japanese origin meaning "fog", due to the angiographic findings in which collateral vessels are formed with changes in flow. There is the possibility of bilateral and progressive stenosis, with consequent occlusion of the distal portion of the internal carotid artery and its branches, and thrombosis, transient repeated ischemia, and intraparenchymal hemorrhages are common findings. Because it is a rare disease, of an etiology not fully described, and because of its clinical repercussions, this case aims to study this pathology and its inclusion as a differential diagnosis of sudden neurological deficit, with a hypothesis of stroke in young patients, especially in carriers of Down Syndrome (DS). Thus, through early diagnosis and its consequent treatment, a better prognosis can be obtained, thus entailing a better quality of life for the patient and his family, and reducing the risk of recurrence.